Investigation of oak wood biochar gasification in downdraft gasifier using aspen plus simulation - ÖZVEREN, UĞUR (My University, 2021)
In response to increasing energy demands and the inevitable release of greenhouse gases into the environment, researchers have turned their attention to biomass energy production. Biomass offers a lot of benefits; however, it has poor calorific value due to its higher moisture and volatile content. Carbonization can be used to overcome this disadvantage and produce biomass with a higher carbon content. One of the most promising thermochemical conversion techniques is gasification. In this study, biochar from oak wood was gasified in a steam environment using Aspen Plus® simulation. The downdraft gasifier model was developed under steady-state equilibrium parameters based on the minimization of Gibbs free energy. As consistent with the literature, H2 was produced higher amount in the steam gasification (55.65%) compared with the air gasification (17.36%). Parametric analyzes were performed to investigate the influence of the operating parameters on the composition of the syngas. Results depicted that the increasing temperature and steam/biochar ratio raised the H2 concentration from 53.21% to 55.72% and 54.50% to 56.84% in syngas respectively. Temperature also showed positive influence on the LHV of syngas that changed between 19620-19708 kJ/kg. The steam/biochar ratio affected the LHV of syngas negatively thus it decreased from 20257 to 18777 kJ/kg.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)